Self-regulated learning strategies of Macau English as a foreign language learners: Validity of responses and academic achievements - Deng, Xiaojia; Wang, Chuang; Xu, Jianzhong (Frontiers in Psychology, 2022)
Self-regulation is important in enhancing students’ academic performance, yet evidence for the systematic and valid instruments to measure self-regulated learning strategies of college students in an English as a foreign language context is far from robust. This study was situated to develop an evaluation tool to examine the status quo of self-regulated learning strategies employed by college English learners and the associations between the use of these strategies and their academic achievement. A large-scale survey was conducted at one university in Macau to provide evidence of the construct validity of responses to the questionnaire on self-regulated learning strategies. Conceptualized in social cognitive theory, the questionnaire comprised environmental, behavioral and personal self-regulated learning strategies with 48 items weaving into 10 dimensions. Strong evidence for reliability and validity was found. Findings also revealed that students who intrinsically valued and used more self-regulated learning strategies achieved higher academic performance. Students in advanced-level English course reported significantly more frequent use of self-regulated learning strategies than students in medium-level and mixed-level English courses. Our results draw attention to the pedagogical orientation for teachers of English as a foreign/second language, in helping students become adaptive learners with self-regulative process.